Abrasive wear resistance of WC-Co and WC-AISI 304 composites by ball-cratering method - Vilhena, L. M.
In the present work, the effect of different binder materials on the tribological properties of cemented carbides was studied. Flat samples of conventional WC-Co, and newly developed WC-AISI 304 stainless steel (SS) composites with and without carbon addition were surface finished by grinding and polishing. Comparative experiments were performed using a ball-cratering tribometer. Worn surfaces were characterized by optical microscopy, surface scanning topography and scanning electron microscopy. It was found that the abrasive wear resistance of the developed WC-SS composites is higher than that of conventional WC-Co and decreases with the carbon addition, in a direct relation with the decreasing hardness. The mechanisms of wear degradation are discussed. (C) 2015 Elsevier B.V. All rights reserved.